Preparation and Characterization of Glass Ceramic Materials from Mixtures of Waste Oyster Shell and Recycled Soda-Lime-Silica Glass - MOHD TAHIR, MOHAMAD AMIR JAMALUDDIN (Enhanced Knowledge in Sciences and Technology, 2022)
Preparation and Characterization of Glass Ceramic (GC) Materials from Mixtures of Waste Oyster Shell (OS) and Recycled Soda-Lime-Silica Glass (SLS) has been reported. The method uses in this research was Solid State Conventional Method and sintered at 900˚C for 2 hours before it has been characterized to study their properties. The data shows that the mass loss increase due to the increasing of the OS content. FTIR analysis show the peak that show the deformation of Si-OH bonding, Si-O-Si bond, bonding of C=O group. From XRD result, the sample indicating crystalline structure which can be seen the clear peak of calcite, quartz, devitrite, and cristobalite crystal phase on the 30OS70SLS sample. The maximum density of the sample was recorded at 2.7049 for powder density and 2.3410 for bulk density with acceptable percentage porosity value 13.47% for sample 30OS70SLS. Besides that, the SEM-EDX showed the existing of pores on the sample and also prove high element of Ca and Si on the 30OS70SLS sample.